2001
DOI: 10.1136/jcp.54.12.940
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic relevance of angiogenesis and mast cells in squamous cell carcinoma of the oesophagus

Abstract: Conclusions-These findings support the suggestion that MVD is a reliable prognostic marker in SCC of the oesophagus. Moreover, MCD may have a role in the angiogenesis of these tumours and might be responsible for their aggressive behaviour. (J Clin Pathol 2001;54:940-944)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
149
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 33 publications
15
149
1
7
Order By: Relevance
“…These findings were in stark contrast to those which were reported in previous studies which were done on various tumours [21][22][23][24][25].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings were in stark contrast to those which were reported in previous studies which were done on various tumours [21][22][23][24][25].…”
Section: Discussioncontrasting
confidence: 99%
“…However, Oleiveira-Neto HH et al found the MCD to be lower in OSCC and in premalignant lesions as compared to that in the normal controls [22]. They attributed it to the migration failure of the mast cells, which possibly reflected a modification in the microenvironment during the tumour initiation and progression.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations